The Latest Strategic Documents Specifying Changes in the Approach to the Modernization of Monuments in Poland - Pałubska, Katarzyna; Zalasińska, Katarzyna (Protection of Cultural Heritage, 2021)
One of the main priorities of all European Union countries, including Poland, is counteracting negative climate change, improving energy efficiency, accessibility of transport infrastructure and public facilities. Tasks identified for implementation in the very short term oblige EU member states to develop and implement strategic documents, specifying ways to cope with the deteriorating state of the environment, infrastructure and activities that discriminate against people with special needs. The article will discuss the most important strategies, plans, projects and planned legislative changes that have a large, but currently difficult to estimate, impact on the protection of historic buildings, including the Strategy for Rehabilitation of Buildings, the New Climate Change Strategy and the Act on Ensuring Accessibility for Persons with Special Needs, the National Railway Programme and EU projects implemented as part of the implementation of these documents in Poland. The article will undertake polemics with the proposals for the modernization and adaptation of historic buildings within the programs supporting the implementation of the priorities mentioned above, showing their degrading influence on the historic stock and the unrealistic implementation of the postulated recommendations in the environment of conservation services. At the same time, the author presents alternative recommendations and possibilities of approaching the problem, indicating the unused potential of historical buildings and proposing solutions which, if recognized in strategic documents, popularized and then financed from alternative sources, could contribute to improving the quality parameters of the indicated priorities.